Dimensions of Situatedness for Digital Public Displays - Rui José; Nuno Otero; Jorge C. S. Cardoso (Advances in Human-Computer Interaction)
Public displays are often strongly situated signs deeply embedded in their physical, social, and cultural setting. Understanding how the display is coupled with on-going situations, its level of situatedness, provides a key element for the interpretation of the displays themselves but is also an element for the interpretation of place, its situated practices, and its social context. Most digital displays, however, do not achieve the same sense of situatedness that seems so natural in their nondigital counterparts. This paper investigates people’s perception of situatedness when considering the connection between public displays and their context. We have collected over 300 photos of displays and conducted a set of analysis tasks involving focus groups and structured interviews with 15 participants. The contribution is a consolidated list of situatedness dimensions that should provide a valuable resource for reasoning about situatedness in digital displays and informing the design and development of display systems.